Tracking isoflavones: From soybean to soy flour, soy protein isolates to functional soy bread - Suqin Shao (Journal of Functional Foods, 2009)
Soybean seeds with three different levels (low, intermediate and high) of isoflavones were processed to soy flour and soy protein isolates (SPIs) and developed into functional soy breads. The effect of factors involved in all steps of the process was investigated by tracking the composition and concentration of native forms of isoflavones. The total isoflavone contents were 8033.3, 10570.1 and 15169.0 nmol/g DM (dry matter) in the three soybeans; 13201.5, 20034.4 and 26014.3 nmol/g DM in defatted soy flours; 9113.2, 13274.6 and 17918.3 nmol/g DM in the SPI; 2782.7, 4081.4 and 5590.3 nmol/g DM in soy breads, respectively. The bread making processes did not affect the total isoflavone content, but changed glucosides/acetylglucosides to aglycones. Malonylglucosides were stable prior to baking but degraded to acetylglucosides and further to glucosides during baking. Our results provide critical information for the production of functional soy breads that contain varying amounts of soy isoflavones.